The Magical Melon - Antud Didi (2015)
This story is based on a Rungus folktale, Tasu Om Parai captured in English for the first time. The Rungus are an ethnic group of Borneo, residing primarily in northern Sabah, Malaysia. The book is a result of a community project aimed at promoting reading and to preserve Rungus lanuguage and culture through stories